THE INFLUENCE OF RECRUITMENT, SELECTION, JOB PLACEMENT AND HR QUALITY ON EMPLOYEE PERFORMANCE PT. PELINDO MULTI TERMINAL BRANCH TANJUNG WANGI - Jessica Nur Faeda; Wardha Nilawati; Rifka Arinda Noviasari (RADJA PUBLIKA, 2024)
This study aims to determine the effect of Recruitment, Selection, Job Placement and HR Quality on Employee Performance. The population and sample of this research are the researchof PT. Pelindo Multi Terminal Branch Tanjung Wangi. Data analysis in the form of validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, (R²) determination tests, and hypothesis tests. The results of this study that the results of the F test sig values of 0.000 < 0.05 and F count > Ftable, which is 12.457 > 2.56 can be interpreted as the influence of Recruitment, Selection, Job Placement and HR that simultaneously (simultaneously) affect the dependent variable, namely employee performance behavior. The Adjusted R Square value of 0.589 or 58.9% means that employee performance is influenced by recruitment, selection, job placement and HR quality while the remaining 41.1% of employee’s performance is influenced by other variables that were not studied in this study